Current Policies and Pedagogies of English Language Teacher Education: Unveiling Social Challenges - Poudel, Ganesh Prasad (Journal of NELTA Gandaki, 2024)
This paper analyzes the current policies and pedagogies of English language teacher education, and the social inequalities associated with English language teaching. It also assesses the challenges of English language teachers to mitigate these social inequalities. It explores the roles and actions that English language teachers could perform to diminish these social inequalities. A review of the concerned literature and policy documents shows that the current policies and pedagogies of English language teacher education in Nepal have focused on the functional-communicative approach to English language teaching. However, the current social inequalities related to English language teaching are gender, class, caste or ethnic background and culture. The challenges for English language teachers are to address social justice and equity issues in multilingual and multicultural contexts. Thus, this study attempts to address social realities in English language teacher education so that it helps to reform current policies and practices. The role and actions of English language teachers should be directed to create critical consciousness.